The Origins and Spread of Domestic Plants in Southwest Asia and Europe. - Colledge, Sue (University College London Institute of Archaeology Publications., 2006)
Leading scholars demonstrate the importance of archaeobotanical evidence in the understanding of the spread of agriculture in southwest Asia and Europe.